(untitled) (Islamic Sciences Journal, 2024)
Praise be to Allah , the Lord of the Worlds, and prayers and peace be upon the most honorable of the prophets and messengers, our Prophet Muhammad, and upon all his family and companions. This topic shows the importance of publicity in marriage in order for the Muslim man and woman to stay away from people’s slander against them, and to stay away from any doubt or suspicion about their relationship. This is why Islam was keen on this and ordered the beating of the tambourine in order to exaggerate the publicity of marriage. This research included an introduction, a preface, and two sections: The first section contains the biography of Imam Saeed bin Mansour and is divided into two sections. The second section contains five topics, and under each topic is a trace, and under each section is its conclusion, mention of evidence and follow-ups, if any, and discussion of its narrators, then judges that effect. The study comes with the most important findings.